„Nieobecny ojciec” – casus rodzin nieletnich przestępców - Bernasiewicz , Maciej; Noszczyk-Bernasiewicz , Monika (Studia Edukacyjne, 2020)
The studies presented in the article show the presence and quality of the male model of the guardian in the life of juvenile delinquents. The biographies of 26 boys and 34 girls (juvenile delinquents) were studied. The text attempts to prove the thesis that the absence of the father in the upbringing of the child (his physical as well as emotional absence) has serious consequences in the children’s moral development. On the other hand, a presence of a criminal father constitutes an equally strong predictor of juvenile delinquency.